2009
DOI: 10.1186/1472-6831-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and cross-cultural validity of a Japanese version of the Dental Fear Survey

Abstract: Background: This study established the reliability and cross-cultural validity of a Japanese version of the Dental Fear Survey (DFS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 9 publications
5
26
1
Order By: Relevance
“…Our study included more participants who reported a minimal frequency of gagging in the clinic and a lower level of dental anxiety. The mean level of DFS among the Japanese population is estimated to be 37.4 ± 14.1 . However, the mean scores of the female and male participants in our study were 33.0 ± 14.5 and 28.6 ± 7.8, respectively.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Our study included more participants who reported a minimal frequency of gagging in the clinic and a lower level of dental anxiety. The mean level of DFS among the Japanese population is estimated to be 37.4 ± 14.1 . However, the mean scores of the female and male participants in our study were 33.0 ± 14.5 and 28.6 ± 7.8, respectively.…”
Section: Discussioncontrasting
confidence: 76%
“…The level of dental fear was assessed using the dental fear survey (DFS), which consists of 20 questions that address anxiety‐provoking situations associated with dental treatment. The Japanese versions of the psychometric tests were used in this study; the validity and reliability of these tests have been previously verified …”
Section: Methodsmentioning
confidence: 99%
“…[7]. The distribution of the items forming these factors was little different from the original DFS and other validated versions of the DFS [57, 12] but was exactly the same as the Japanese version of the DFS [10]. …”
Section: Discussionmentioning
confidence: 96%
“…The DFS was cross-culturally adapted and validated among Brazilian psychology undergraduates [19] with higher DFS scores associated with longer intervals between dental visits. The DFS has been translated and validated for application in a range of different countries [10,16,20,21,22,23,24]. Furthermore, the DFS has been used to assess dental fear before dental treatment under sedation, and in the study of dental phobias [10,24].…”
Section: Introductionmentioning
confidence: 99%